COMMUNITY EDUCATION IN OVERCOMING STIGMATIZTION FAMILY WITH MENTAL DISORDERS IN THE AGRICULTURAL AREA OF MOJOPARON PASURUN REGENCY - Evy Aristawati; Bagus Dwi Cahyono; Nurul Huda (UNEJ e-Proceeding, 2022)
Psychosocial problems are problems that occur in the mental and social. Stigmatization of people with mental disorders is still common. Stigmatization about people with mental disorders who are considered dangerous and families who feel ashamed and worried about having family members with mental disorders, often lead to social isolation or intentionally isolate people with mental disorders by shackles. The purpose of counseling is to increase family knowledge about the importance of avoiding stigmatization in people with mental disorders. Counseling is done by providing education and leaflets according to the theme. Based on the results of the pre-survey conducted before this outreach activity, family knowledge about the importance of avoiding stigmatization in people with mental disorders was respondents with low knowledge (60%) and with sufficient knowledge (40%). After providing education, it was found that there was a significant increase in the knowledge of family members: enough (40%), good (60%). Keywords: education, community, stigmatization, mental disorders